Design of alternative inhaler system to improve the delivery of inhaled pharmaceutical aerosol (IPA) - Md Tasyrif, Abdul Rahman; Ahmad Faizal, A. Salleh; Sazali, Yaacob; Hazlinda, Razali (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.